Iván Rodríguez Chávez and his reading of Vallejian justice - Jiménez Moreno, Manuel de J. (2023)
This essay provides an introductory guide to the contributions that Ivan Rodriguez Chavez, Rector of the Ricardo Palma University, led the Law and Literature Movement in Peru. Under this tenor, the central axis of reflection that guides the present investigation lies in offering a look at the notion of justice in Rodriguez Chavez, which later is linked to Vallejian poetic justice. Starting from the justice classes, the author made a reading in iuspoetic key of four poems by César Vallejo, analyzed in his essay "Justice in Vallejo's poetry". Namely: "Our bread", poem XXIII by Trilce, "Black stone on a white stone" and "Hymn to the volunteers of the Republic".